Students evaluation of the University of the Philippines at Los Banos service physical education program - Lucas, Roman L. 1924- (1974)
The adequacy of the provisions and conditions for departmental philosophy, program of activities, equipment and facilities and evaluation procedures in the college service physical education program of the University of the Philippines at Los Banos (UPLB) as evaluated by the students of the physical education department was determined in this study.
Thesis (M.A.T. Physical Education)--University of the Philippines.
Keywords: University of the Philippines -- Los Banos; Physical education and training